Transdisciplinary complexity science: deepening system understanding for sustainability - Jager, Lynn A. de; Bal, Michèlle; Baudena, Mara; Van den Broek, Karlijn; Davis, Natalie; Dijkstra, Henk A.; Dorresteijn, Ine; Kamphuis, Carlijn B. M.; Lykourentzou, Ioanna; Mayor, Ángeles G.; Omodei, Elisa; Alvial Palavicino, Carla; et al. (Humanities and Social Sciences Communications, 2025)
The complex and contextual nature of sustainability challenges demands an approach that integrates quantitative complexity science with transdisciplinary approaches to create an integrated understanding of system change. We present a systematic literature analysis from an emerging field we term Transdisciplinary Complexity Science for Sustainability and derive best practices for how this research approach can foster learning and action for sustainability. Based on our analyses, we identify key areas for future research and provide concrete recommendations for carrying out Transdisciplinary Complexity Science for Sustainability.